CORRELATION BETWEEN CENTRAL CORNEAL THICKNESS (CCT) AND RETINAL NERVE FIBER LAYER THICKNESS (RNFL) IN PRIMARY OPEN ANGLE GLAUCOMA - Dr. Wasim Rashid; Dr. Mustafeez Zehra; Dr. Sheikh Sajjad Ahmed; Dr Areeb (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objectives:  To correlate central corneal thickness and retinal nerve fibre layer thickness in patients with primary open angle glaucoma and compare it with their age matched controls using Ocular Coherence Tomography (OCT).Material and Methods: This is an observational cross-sectional study in which 127 eyes of 100 patients diagnosed with POAG and 200 eyes of 100 controls were included. Ocular coherence tomography (OCT) was used to estimate Central Corneal Thickness (CCT) and Retinal Nerve Fiber Layer (RNFL) thickness in both glaucoma and control groups and correlated. Statistical analysis was done using Pearson’s coefficient and p value < 0.005 was considered statistically significant.Results: The average CCT among POAG cases was 505.7 µm whereas that of controls was 550.5 µm. Average RNFL thickness in POAG group was found to be 67.5± 15.70 µm whereas that in controls was 90.8± 7.89 µm. A positive significant correlation between CCT and average RNFL thickness was found in patients with POAG.Conclusion and Implications: The results of this study add to the evidence that patients with thinner corneas have greater susceptibility to glaucomatous damage in view of thin RNFL. With the increasing availability of the OCT, CCT and RNFL measurements may be considered useful ancillary investigative tool in patients with POAG, for early diagnosis and timely management.